ANALISIS STRATEGI USAHA KECIL MENENGAH (UKM) INDONESIA BERDAYA UNGGUL SEBAGAI UPAYA MEMASUKI BISNIS GLOBAL PADA UKM NOQTAH ART TANGERANG SELATAN BANTEN - Vera Maria Iskandar; Muhammad Asyim Fajr (Jurnal Cakrawala Ilmiah, 2023)
Small and Medium Enterprises (SMEs) have proven to be an important pillar in contributing to the Indonesian economy, by being able to contribute to GDP growth of 61.07%. With the increasingly massive growth of SMEs, the right strategy is needed so that SMEs have superior power to compete in the domestic context or even to enter global business. This global business can be used as a momentum and opportunity for SMEs to be able to develop their business to become superior. Of course, in entering this global business scope, the right strategy is needed. This study in the form of an article uses a descriptive method with literature study as a data collection technique by collecting from various literature as a basis for arguments. Through this article, it also tries to investigate and analyze the right strategy to be applied to Noqtah Art SMEs in entering the global business sphere which has better future business prospects.